REDD+ Application in Southeast Asia: Legal Challenges and Indigenous Peoples’ Rights in Climate Change Mitigation - Adrian Nugraha; Joni Emirzon; Muhammad Azil Maskur; Robert Lihtorng Chen (Universitas Negeri Semarang, 2026)
Indigenous peoples, whose cultural and ecological connections to forests are profound, are disproportionately affected by climate change and related mitigation initiatives, including REDD+ (Reducing Emissions from Deforestation and Forest Degradation). This study critically examines the protection of Indigenous peoples’ rights in REDD+ application across Southeast Asia, with particular attention to disparities in legal recognition, stakeholder engagement, and the application of Free, Prior, and Informed Consent (FPIC). Employing a doctrinal legal research methodology, the analysis draws on primary sources—such as international treaties, national constitutions, statutory regulations, and REDD+ strategies—and secondary sources, including UN and FAO reports, to evaluate both legal frameworks and practical safeguards. The findings indicate that while some countries (e.g., Indonesia, the Philippines, Cambodia, and Myanmar) formally recognize Indigenous peoples, participation mechanisms and FPIC enforcement remain limited; others (e.g., Malaysia, Thailand, Vietnam, and Laos) lack explicit recognition, leaving significant gaps in rights protection. The study concludes that effective REDD+ application requires harmonized treaty interactions, strengthened domestic safeguards, and the integration of Indigenous worldviews into policymaking. It recommends inclusive, rights-based approaches that position Indigenous communities as active partners, promoting both ecological sustainability and social justice.